Socialization of Sports in the New Age - Utepbergenov Genjabay Kutlimurotovich (Research Parks Publishing LLC, 2021)
The aim of this article is to discover the positive aspects of physical education and sport. In the article a philosophical consideration and analysis of sport as a means of spiritual enritual enrichment of young people in society have wade.